Four-dimensional differential equations for the leading divergences of dimensionally-regulated loop integrals - Henn, Johannes; Ma, Rourou; Yan, Kai; Zhang, Yang (The journal of high energy physics, 2023)
A bstract We invent an automated method for computing the divergent part of Feynman integrals in dimensional regularization. Our method exploits simplifications from four-dimensional integration-by-parts identities. Leveraging algorithms from the literature, we show how to find simple differential equations for the divergent part of Feynman integrals that are free of subdivergences. We illustrate the method by an application to heavy quark effective theory at three loops.